Potassium channels on smooth muscle as a molecular target for plant-derived Resveratrol - Rajkovic, Jovana; Djokic, Vladimir; Gostimirovic, Milos; Gojkovic-Bukarica, Ljiljana; Martorell, Miquel; Sharifi-Rad, Javad; Novakovic, Radmila (Cellular and Molecular Biology, 2020)
Resveratrol (3,5,4'-trihydroxy-trans-stilbene) is a phytoalexin present in a variety of plant species. Resveratrol has a wide spectrum of pharmacologic properties, and it exhibits versatile biological effects on different human and animal models. The studies have shown that potassium (K) channels can be potential targets in the mechanism of resveratrol action. K channels play a crucial role in maintaining membrane potential. Inhibition of K channels causes membrane depolarization and then contraction of smooth muscles, while the activation leads to membrane hyperpolarization and subsequently, relaxation. Five diverse types of K channels have been identiï¬ed in smooth muscle cells in different tissue: ATP-sensitive K channels (KATP), voltage-dependent K channels (Kv), Ca2+ - and voltage-dependent K channels (BKCa), inward rectiï¬er K channels (Kir), and tandem two-pore K channels (K2P). The expression and activity of K channels altered in many types of diseases. Aberrant function or expression of K channels can be underlying in pathologies such as cardiac arrhythmia, diabetes mellitus, hypertension, preterm birth, preeclampsia, and various types of cancer. Modulation of K channel activity by molecular approaches and selective drug development may be a novel treatment modality for these dysfunctions in the future. The plant-derived non-toxic polyphenols, such as resveratrol, can alter K channel activity and lead to the desired outcome. This review presents the basic properties, physiological, pathophysiological functions of K channels, and pharmacological roles of resveratrol on the major types of K channels that have been determined in smooth muscle cells.